Structure and Optical Properties of Transparent Cobalt-Doped ZnO Thin Layers - Piotr Potera; Ihor S. Virt; Bogumił Cieniek (Applied Sciences, 2023)
Transparent thin layers of cobalt-doped ZnO were produced with the pulsed laser deposition method. The cobalt content of the original solid solution was 20% at. The crystallographic structure was examined by X-ray diffraction, which showed that the fabricated layers crystallized in the wurtzite phase and had a dominant orientation along the a-axis. The texture coefficient (increasing from F = 0.08 for the non-annealed layer to F = 0.94 for the annealed layer at 400 °C) and grain size (D = 110 ÷ 140 nm) were calculated. Optical constants, such as the refractive index n (1.62) and the extinction coefficient k (0.1 ÷ 0.4), were determined from the ultraviolet–visible–near-infrared transmission spectrum using the envelope method. The value of the optical band gap was determined, which is lower than for pure ZnO. Increasing the annealing temperature of the ZnO:Co layer increases the Urbach energy from 0.20 to 0.25 eV, which shows the difference in the type of growth defects in the ZnO matrix.